A hitelintézetek és az állam szerepe az otthonteremtésben- fókuszban az OTP Bank - Axnix Judit (2015)
For my thesis I was looking for a topic that is constantly relevant in our society in some way. One of these topics is the area of home buying. Nowadays, very few people start to achieve their real estate goals without any external help, should they be the construction of a new apartment or the enlargement of an existing one. The reason for this is the low level of income and the high market prices. The goal of my thesis is to provide widespread information on the actual housing benefits and mortgage possibilities in a descriptive manner. Firstly I describe the process of getting a loan, with a special attention to the com-pulsory requirements, to the tasks to be fulfilled from informing the clients until the moni-toring. In thesis the loan related costs, fees and the other banking service related discounts are also mentioned. Secondly, the topic of the housing benefit supported by the government is described. In this part I examine in a detailed way the housing loans with interest subsidy, the non-refundable subsidies, like the social housing subsidy and at last but not least the importance of the building society savings accounts. I did not only describe government supported housing benefits, I tried to highlight both its positive and the negative sides, where I used the experience I have gained during my internship. As for the negative side, I mentioned the requirements from the bank´s side, the long administration process, and the high costs and fees of providing a loan. Examining the go-vernmental support it can be realized that the amount of the subsidy is not in accordance with the actually existing costs, as an example we can consider the costs of building mate-rials in case of a newly built apartment or the high real estate prices. As for the positive side, I highlighted the reformed social housing subsidy that is called “Home buying bene-fits for families” and also the 30% governmental subsidy on the building society savings accounts. Furthermore I also introduced the tax-free benefit provided by the employer that is a part of the cafeteria benefits. This is a non-state subsidy that can be requested since 2014. This possibility can be used by the employers to support their employees to pay back an open mortgage or to help with the payment of the respective installments. With the help of my questionnaire I also present how the above described subsidies are working and can be used in the real life.